Design, Construction and Ocean Testing of Wave Energy Conversion System with Permanent Magnet Tubular Linear Generator - 陈中显 余海涛 刘春元 洪立玮 (Transactions of Tianjin University, 2016)
In this paper, the design, construction and ocean testing of a wave energy conversion system are studied. Based on the motion characteristics of double buoys in ocean waves, a wave energy conversion system with permanent magnet tubular linear generator （PMTLG） is proposed to convert ocean wave energy into electricity. The wave energy conversion system was installed in the Yellow Sea near Lianyungang, China. The ocean test re- suits indicate that it had dynamic and static performance, and obtained an expected amount of electricity. The calcu- lation result indicates the average output power was about 1 000 W, and the conversion efficiency from wave en- ergy into electricity was 1.4%. In addition, the wireless data communication, mechanics and oceanography were also discussed.